X-Band Phased-Array Transmitter Architecture with Power Transfer Optimization Algorithm for Space Solar Power System: A Case Study - Clark, Mitchell; Raguso, Thomas; Alexaner, James; Buhr, Troy; Karsilayar, Aydin; Silva-Martinez, Jose (Conference proceedings : Midwest Symposium on Circuits and Systems, 2024)
Space-based solar power is a proposed source of uninterrupted renewable energy, with power generated in space and beamed to an earth-based receiver. This paper describes a scalable transmission and calibration system for space-based solar power. The transmitter is composed of a grid of individually controlled subarrays, each containing a 400-element uniform phased array of microstrip patch antennas. Each sub array is further equipped with a phase locked loop to generate the 10 GHz transmission signal, programmable phase shifters to modify beam direction, power amplifiers to drive antennas, and supporting control logic. The control logic provides the interface for a specialized calibration algorithm that utilizes power transmission data to continuously calibrate sub arrays for correcting beam direction and minimizing beam width. A behavioral model of the system was then produced, with results indicating over 84 % of the radiated power reaching a 2 km by 2 km target 36000 km away. Additionally, the transmitter model was capable of converging the beam to points with an angular resolution far exceeding the phase shifter resolution.